Evaluation of empirical equation for flow duration curve and water table at drained peat catchment in Johor Malaysia - Sahlan Jamudding, 1991-, author; Muhamad Askari, Dr., supervisor; Fakulti Kejuruteraan Awam (Johor Bahru : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2014